Development of rural areas in cultural landscape - Krupnik, K.; Brozek, M. (Видавництво Національного університету "Львівська політехніка", 2007)
Study notion of cultural landscape that was raised in this dissertation has a long tradition. The interest of this subject matter has grown up recently in Poland. 11 was due to large investigative and applicable possibilities for cultural landscape research. \t is all because of neglecting, for a period of above 50 years this sphere of activities, and as a result need of critical glance on Polish realities shaped in a post-war period as well as during the decade of dynamic constitutional and economic transformations. The works concerning formation of the rural areas landscapes are one of the ways to open science on aims and practical undertakings. They show directions, options of how to work on the areas of communes, likewise local plans of spatial farm implementing are helpful in the studies on influence of environment or plans of legal protection of terrains. The new pattern of the conduct is created, which is engaged in the processes of environmental changes. \t has a large practical impact and a strong influence on reviving local matters and self-governance.